2020
DOI: 10.1111/ped.14146
|View full text |Cite|
|
Sign up to set email alerts
|

Metered‐dose inhaler ipratropium bromide for children with acute asthma exacerbation: A prospective, non‐randomized, observational study

Abstract: Background Ipratropium bromide (IB), when administered with β2‐agonists, is effective in reducing hospital admissions of children presenting to the emergency department (ED) with severe asthma. While IB is commonly delivered in its nebulized form, using a metered‐dose inhaler (MDI), can, reportedly, shorten patients’ length of stay in the ED. However, the effectiveness and safety of IB administration using an MDI with a spacer have not been established. This study aimed to investigate the effectiveness and saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…7 , 11 – 13 , 15 , 16 Finally, several guidelines extrapolate the benefits of MDI and spacer with salbutamol with emerging evidence suggesting that ipratropium bromide delivered in this fashion does not reduce admission rates. 7 , 11 , 15 , 71 , 72 …”
Section: Resultsmentioning
confidence: 99%
“…7 , 11 – 13 , 15 , 16 Finally, several guidelines extrapolate the benefits of MDI and spacer with salbutamol with emerging evidence suggesting that ipratropium bromide delivered in this fashion does not reduce admission rates. 7 , 11 , 15 , 71 , 72 …”
Section: Resultsmentioning
confidence: 99%
“…Several studies report safety information linked to the use of inhaled ipratropium bromide in the pediatric population with asthma. In a prospective observational study investigating the safety of ipratropium bromide in pediatric asthma exacerbations, Nomura et al reported a single case of mild vomiting among the 77 children treated [ 74 ]. This isolated finding suggests that emesis may be a rare AE associated with ipratropium bromide use; however, further research is necessary to establish a definitive link.…”
Section: Data Safety Of Short-acting Bronchodilator Administration In...mentioning
confidence: 99%
“…This isolated finding suggests that emesis may be a rare AE associated with ipratropium bromide use; however, further research is necessary to establish a definitive link. The observed AE, mild vomiting, was infrequent and categorized as the mildest grade on the Common Terminology Criteria for Adverse Events (CTCAE) scale, indicating its minimal impact on the patient's overall well-being [ 74 ]. The favorable safety profile observed in this study is consistent with findings from a Cochrane Systematic Review, which reinforces the established safety and efficacy of ipratropium bromide in pediatric asthma treatment [ 37 ].…”
Section: Data Safety Of Short-acting Bronchodilator Administration In...mentioning
confidence: 99%
“…9 Another study from Japan also showed no benefit. 10 In summary, there is no evidence to support the use of inhaled salbutamol or IB administered as MDI in the acute management of children with moderate to severe wheeze. The administration of two drugs by MDI…”
Section: Salbutamol+ib Administered Via MDImentioning
confidence: 99%